Pengembangan Media Monopoli Pop-Up untuk Meningkatkan Literasi Budaya Siswa Kelas V Sekolah Dasar - Deviana Seftia Ferawati; Diyanti Jati Pratiwi; Nanda William (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
In the era of globalization, strengthening cultural literacy has become an important goal of elementary education. However, cultural literacy learning remains suboptimal due to the limited use of innovative and interactive learning media. This study aimed to develop a cultural literacy-based Pop-Up Monopoly learning media and examine its validity, practicality, and effectiveness in improving the cultural literacy of fifth-grade elementary school students. This Research and Development (R&D) study employed the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation phases. The participants were 55 fifth-grade students from SDN 5 Bendorejo, SDN 1 Kedunglurah, and SDN 2 Kedunglurah, Trenggalek Regency. Data were collected through interviews, documentation, questionnaires, validation sheets, and cultural literacy tests. The developed media obtained validation scores of 92% from material experts, 96% from language experts, 91% from media experts, and 95% from practitioner validators, with an overall average of 93%, indicating that it was highly valid. Teachers and students also provided very positive responses, demonstrating the media's practicality. The average student score improved from 57.4 on the pre-test to 84.5 on the post-test. Furthermore, the Paired Sample t-Test showed a significant difference between pre-test and post-test scores (Sig. = 0.000 < 0.05), while the N-Gain value of 65% indicated that the media was effective in enhancing students' cultural literacy. Therefore, the cultural literacy-based Pop-Up Monopoly learning media is valid, practical, and effective for elementary school learning.